The Transformation of Airline Distribution: From Legacy Documents to Dynamic Retail Models - Mukul Kumar Gaur (International Journal of Computational and Experimental Science and Engineering, 2026)
The airline industry is undergoing a fundamental transformation in its distribution architecture, moving away from legacy document-based systems that have dominated commercial operations since the 1960s toward modern, offer-centric retail models. Traditional distribution relies on fragmented architectures that distribute commercial information across multiple independent documents including passenger name records, electronic tickets, and ancillary service documentation, creating operational inefficiencies and constraining commercial flexibility. This fragmentation limits airlines’ ability to implement dynamic pricing, personalized offers, sophisticated bundling strategies, and real-time merchandising capabilities that are standard in contemporary digital commerce. The emerging paradigm introduces two core constructs: dynamic commercial propositions generated in real-time based on customer context and travel requirements, and unified commercial records that consolidate all transaction information into single authoritative sources throughout the customer journey. This transformation enables airlines to operate as sophisticated digital retailers capable of implementing continuous pricing strategies, customer-centric value optimization, and seamless omnichannel experiences. The shift represents more than technological modernization; it requires comprehensive organizational transformation including evolution of commercial teams from inventory managers to retail strategists, significant investment in analytical infrastructure and decision-support systems, and fundamental reconceptualization of revenue management from capacity-focused optimization to multidimensional value creation that balances immediate transaction revenue with long-term customer relationship development. Research demonstrates that modern distribution capabilities enable substantial improvements in operational efficiency, servicing simplification, merchandising effectiveness, and revenue capture through enhanced personalization, dynamic bundling, and ancillary service optimization across all distribution channels.